Triple-functional carbon fibre reinforced polymer for strengthening and protecting reinforced concrete structures. (April 2021) - Wei, A.; Al-Ameri, R.; Koay, Y.C.; Tan, M.Y.J.
Abstract: Carbon fibre reinforced polymers (CFRP) are innovative composite materials that have been applied for repairing and retrofitting civil engineering structures. In this work, long-term performance tests have demonstrated that the CFRP can not only perform as a strengthening material for reinforced concrete (RC), but also can simultaneously perform as a protective coating layer and an impressed current cathodic protection (ICCP) anode for protecting steel rebar from corrosion. It is shown that the CFRP coating layer is partially protective, reducing steel rebar corrosion and ICCP current requirements. A reduced ICCP current density of 20 mA/m 2 avoided ICCP induced CFRP damage, permitting long-term protection and strengthening of RC structures. Highlights: Long-term immersion tests demonstrate triple functions of a CFRP based coating layer. CFRP coating layer is partially protective and reduces the current requirement for effective ICCP. CFRP performs as a protective coating, a strengthening material and an ICCP anode for RC structures.